The Lewis Base Stabilized Parent Arsanylborane H2AsBH2⋅NMe3. Issue 36 (31st July 2013) - Marquardt, Christian; Adolf, Ariane; Stauber, Andreas; Bodensteiner, Michael; Virovets, Alexander V.; Timoshkin, Alexey Y.; Scheer, Manfred
<x xml:space="preserve">Abstract</x> Exclusively hydrogen‐substituted arsanylboranes: The synthesis of the unprecedented Lewis base stabilized monomeric parent compound of the arsanylborane H2AsBH2⋅NMe3 was achieved in a one‐pot reaction in high yield and purity. The analogous phosphanylborane was synthesized in a similar manner. A series of different reactions was performed on H2AsBH2⋅NMe3 to show its broad reactivity pattern.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>